Plating Method
The laminated Cr plating method on a hard Cr base layer addresses the challenges of hardness and corrosion resistance, ensuring a durable black aesthetic and heat resistance, particularly in demanding environments.
Patent Information
- Application Number
- JP2020189920
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-14
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2040-11-14
AI Technical Summary
Existing methods for laminating Cr plating on nickel plating struggle to achieve high hardness, excellent corrosion resistance, and maintain a unique black aesthetic appearance without discoloration or cracking, especially in harsh environments.
A plating method involving a hard Cr plating layer as a base followed by a black Cr plating layer, using specific concentrations of chromic acid anhydride, barium carbonate, magnesium silicofluoride, sodium nitrate, and phosphoric acid, with controlled current density and temperature, to create a laminated Cr plating structure.
The method achieves excellent corrosion resistance, high hardness, and maintains a beautiful black color without discoloration, even in harsh conditions, with improved adhesion and resistance to cracking and peeling.
Smart Images

Figure 0007602786000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a plating method for providing a Cr plating layer on the surface of a base metal. [Background technology]
[0002] Cr plating is electrochemically deposited on the surface of base metals such as iron and iron alloys to improve corrosion resistance, aesthetics, wear resistance, etc., and is therefore used in the surface treatment of various metals (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 11-267254 [Patent Document 2] Japanese Patent Application Publication No. 8-283962 Summary of the Invention [Problem to be solved by the invention]
[0004] In Patent Document 1, in order to improve the corrosion resistance of the surface of a golf club head, a nickel plating layer is formed as an underlayer on the surface of the head, and a Cr plating layer is laminated on top of this. Patent Document 2 describes a method of laminating a nickel plating layer and a black Cr plating layer as masking layers on the surface of stainless steel to decorate the surface of stainless steel by ion plating with a titanium-based compound. The above publications disclose a method of providing a nickel plating on a Cr plating base, but it is difficult to achieve excellent hardness and corrosion resistance with a plating layer in which a Cr plating is laminated on a nickel plating.
[0005] The present invention was developed with the aim of eliminating the above-mentioned problems, and an important object of the present invention is to provide a plating method which realizes high hardness and excellent corrosion resistance while realizing the unique aesthetic quality of black on the surface, which maintains a beautiful black color for a long period of time without corrosion even in harsh usage environments, and which also realizes heat resistance that does not discolor at high temperatures.
[0006] A plating method according to one embodiment of the present invention includes a hard Cr plating step of providing a hard Cr plating layer on the surface of a base metal, and a black Cr plating step of providing a Cr plating layer by laminating a black Cr plating layer on the hard Cr plating layer as a base plating layer after the hard Cr plating step. In the black Cr plating process, a plating bath containing 350 g / L to 450 g / L of chromic anhydride, 5 g / L to 13 g / L of barium carbonate, 0.1 g / L to 0.2 g / L of magnesium silicofluoride, 2 g / L to 5 g / L of sodium nitrate, and 6 mL / L to 12 mL / L of an aqueous solution of phosphoric acid with a concentration of 85 wt% was used, and the current density was set at 25 A / dm 2 or 35A / dm 2 、 The solution temperature is set to 15°C to 25°C, and the plating time is set to 5 to 20 minutes to form a black Cr plating layer.
[0007] The above plating method realizes the unique aesthetics of black color with the black Cr plating layer on the surface, while by laminating a hard Cr plating layer as an underlayer and a black Cr plating layer on the surface, it realizes excellent corrosion resistance that cannot be achieved with a hard chrome plating layer alone, and maintains a beautiful black color for a long time without corrosion even in harsh usage environments. Furthermore, by forming a black Cr plating layer on the surface using a hard Cr plating layer as an underlayer, it also achieves excellent high hardness and heat resistance that does not discolor at high temperatures.
[0008] The enlarged cross-sectional view of Figure 1 shows the hard Cr plating layer 2 and black Cr plating layer 3 laminated on the surface of the base metal 1 in the above process. The hard Cr plating layer 2 formed on the surface of the base metal 1 in the hard Cr plating process has numerous cracks (cracks 4) on its surface. The cracks 4 cause a decrease in corrosion resistance, but the black Cr plating layer 3 laminated on the surface of the hard Cr plating layer 1 is less likely to crack, and penetrates into the cracks 4 of the hard Cr plating layer 1 to improve corrosion resistance, and further strengthens the adhesion of the black Cr plating layer 3 through its anchor effect, making the surface beautiful and smooth.
[0009] The above plating method achieves features that could not be achieved by a hard Cr plating layer alone, namely, the unique aesthetics of black and excellent corrosion resistance, maintaining a beautiful black color for a long time without corrosion even in a harsh usage environment, and furthermore, in addition to high hardness, heat resistance that does not discolor at high temperatures of 400°C or more is achieved. The features of the above plating method are achieved by a unique method of laminating a black Cr plating layer on the surface of a hard Cr plating layer as an underlayer. The present inventor has developed a plating method of laminating a hard Cr plating layer on the surface of a black Cr plating layer to achieve excellent corrosion resistance. However, this plating method cannot achieve the unique aesthetics of black because the hard Cr plating layer is laminated on the surface of the black Cr plating layer, and further, because a thick hard Cr plating layer is laminated on the surface of the underlayer black Cr plating layer, there is a drawback that the surface is easily cracked by impacts such as bending and pressing. In contrast, the above plating method uses a hard Cr plating layer as an underlayer and a black Cr plating layer is laminated on the surface of the hard Cr plating layer, thereby achieving a unique aesthetics of a black surface while achieving excellent corrosion resistance and heat resistance that does not discolor at high temperatures.
[0010] In particular, the above plating method laminates a black Cr plating layer on a hard Cr plating layer as a base layer, and uses Cr plating layers as both the base layer and the surface layer. This results in excellent complementarity between the base layer and the surface layer, with the hard Cr plating layer as the base layer realizing high hardness characteristics, and the black Cr plating layer on the surface realizing extremely excellent corrosion resistance and heat resistance in addition to the unique aesthetic quality of black that cannot be achieved with a hard Cr plating layer.
[0011] Even in accelerated salt water testing in which the above metal plates were directly sprayed with 5 wt% salt water, the rating number after 150 hours was 9.8 (rust occurrence rate of 0.02% or less), and after 200 hours the rating number was 9.7, showing almost no change, demonstrating extremely excellent corrosion resistance.
[0012] The corrosion resistance test was performed with a temperature / humidity of 49°C / 95%, and the state of rust formation was inspected after 24 hours, 48 hours, 72 hours, 96 hours, 168 hours, 336 hours, 504 hours, and 700 hours. The salt water acceleration test was performed in a 35°C temperature environment, where 5 wt% salt water was sprayed directly onto the test specimens so that the salt water adhered to the surface of the test specimens, and the state of surface rust after 150 hours was inspected.
[0013] Furthermore, the above metal plates were pressed and bent to a radius of curvature of 5 mm, and no peeling or cracking of the surface plating was observed, and they also showed extremely excellent properties in the impact of the press processing. In order to prevent peeling or cracking of the plating, the metal plates to be bent are hard Cr-plated on the surface after bending, but since cracks and peeling do not occur during bending with a press, the above plating method has the advantage that by plating a flat metal plate and then bending it, the metal plate can be plated efficiently and efficiently, and then bent to reduce the manufacturing costs of products with plated surfaces.
[0014] Furthermore, metal plates processed by the above plating method have excellent heat resistance and do not discolor even when heated to 400°C, making them suitable for use in applications that require heat resistance, such as car mufflers and exhaust pipes, and they also have the advantage of maintaining their beautiful black surface color for a long period of time.
[0015] Furthermore, the above plating method shows that the black chrome plating layer on the surface has excellent adhesion. In this test, a cloth tape with an adhesive layer was attached to the surface of the black Cr plating layer and pressed firmly for 10 seconds. The cloth tape was then instantly peeled off and the state of the plating film adhering to the surface of the cloth tape was visually observed. Furthermore, peeling and swelling of the plating film on the surface of the base metal where the cloth tape was peeled off was visually observed.
[0016] In the adhesion test, the plating method of the present invention did not result in any plating film adhering to the surface of the peeled cloth tape, and no peeling of the plating film or blistering occurred at the peeled portion of the cloth tape.
[0017] In a plating method according to another embodiment of the present invention, the black Cr plating layer is thinner than the hard Cr plating layer, and has a thickness of 0.1 μm or more and less than 10 μm.
[0018] In a plating method according to another aspect of the present invention, the thickness of the hard Cr plating layer is set to be 1 μm or more and 50 μm or less.
[0019] In a plating method according to another embodiment of the present invention, in the black Cr plating step, a plating bath containing 350 g / L to 450 g / L of chromic anhydride, 5 g / L to 13 g / L of barium carbonate, 0.1 g / L to 0.2 g / L of magnesium silicofluoride, 2 g / L to 5 g / L of sodium nitrate, and 6 mL / L to 12 mL / L of an aqueous solution of phosphoric acid with a concentration of 85 wt% is used, and a current density of 25 A / dm 2 or 35A / dm 2 The solution temperature is set to 15°C to 25°C, and the plating time is set to 5 to 20 minutes to form a black Cr plating layer.
[0020] In a plating method according to another embodiment of the present invention, 10 g / L to 20 g / L of oxalic acid and 1 g / L to 5 g / L of trivalent chromium are added to the plating bath in the black Cr plating step.
[0021] In a plating method according to another embodiment of the present invention, the amount of chromic anhydride added in the black Cr plating step is 360 g / L to 420 g / L.
[0022] In a plating method according to another embodiment of the present invention, the amount of barium carbonate added in the black Cr plating step is 8 g / L to 10 g / L.
[0023] In a plating method according to another embodiment of the present invention, the amount of magnesium silicofluoride added in the black Cr plating step is 0.15 g / L to 0.17 g / L.
[0024] In a plating method according to another embodiment of the present invention, the plating time in the black Cr plating step is 8 to 15 minutes. [Brief description of the drawings]
[0025] [Figure 1] FIG. 2 is an enlarged cross-sectional view showing the surface state of a base metal plated with Cr by a plating method according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The present invention will be described in detail below with reference to the drawings. In the following description, terms indicating specific directions or positions (e.g., "upper", "lower", and other terms including these terms) are used as necessary, but the use of these terms is for the purpose of facilitating understanding of the invention with reference to the drawings, and the meanings of these terms do not limit the technical scope of the present invention. In addition, parts with the same reference numerals appearing in multiple drawings indicate the same or equivalent parts or members. Furthermore, the embodiments shown below are specific examples of the technical ideas of the present invention, and do not limit the present invention to the following. Furthermore, unless otherwise specified, the dimensions, materials, shapes, relative positions, etc. of the components described below are intended to be illustrative and not to limit the scope of the present invention. Furthermore, the contents described in one embodiment or example can be applied to other embodiments or examples. Furthermore, the sizes and positional relationships of the components shown in the drawings may be exaggerated to clarify the explanation.
[0027] (Embodiment 1) The present invention is a plating method for providing a black Cr plating layer on the surface of a base metal via an undercoat plating layer, in which the undercoat plating layer is a hard Cr plating layer and the black Cr plating layer is laminated on the surface of the hard Cr plating layer. After the surface of the base metal is pretreated, a hard Cr plating layer is attached to the base plating layer in a hard Cr plating process, and then the hard Cr plating layer is laminated on the hard Cr plating layer in a black Cr plating process to produce a black Cr plating layer. In the pretreatment process, the base metal surface is immersed in a degreasing solution to remove oil components attached thereto, then washed with water to remove the degreasing solution, and then washed with water, followed by a general activation treatment and washing with water.
[0028] The base metal is a metal such as iron, zinc, copper, aluminum, or an alloy thereof, stainless steel, or the like.
[0029] The hard Cr plating layer is electrodeposited on the surface of the pretreated base metal by a conventional hard Cr plating method. In this plating process, for example, 200 g / L to 300 g / L of chromic anhydride and 2 g / L to 3 g / L of sulfuric acid are added to the plating bath. The current density is preferably 25 A / dm 2 or 50A / dm 2 The deposition rate can be increased by increasing the current density, but this affects the deposition shape and reduces the surface smoothness, so for example, a current density of 40 A / dm 2 The thickness of the hard Cr plating layer is preferably 1 μm or more, more preferably 10 μm or more, and is preferably 50 μm or less, more preferably 40 μm or less. The durability can be improved by increasing the thickness of the hard Cr plating layer, but the smoothness decreases and the plating cost increases, so the thickness is set to an optimal value taking into consideration the application.
[0030] In the present invention, the plating bath and plating conditions for forming the hard chrome plating layer can be those known in the art. For example, the plating bath is a fluoride bath containing fluoride, and the current density is 40 A / dm 2 Alternatively, the temperature may be 55°C.
[0031] In the black Cr plating process, a black Cr plating layer is applied to the surface of the hard Cr plating layer through the following process. Black Cr plating is a plating process that turns black by oxidizing chromic anhydride. The black Cr plating layer is excellent in corrosion resistance, wear resistance, and heat resistance, so it is provided on the surface to protect the base metal. The plating bath in the black Cr plating process contains magnesium silicofluoride, sodium nitrate, and phosphoric acid in addition to chromic anhydride and barium carbonate. The amount of chromic anhydride added to the plating bath is preferably 350 g / L to 450 g / L. More preferably, the amount of chromic anhydride added to the plating bath is 360 g / L to 420 g / L.
[0032] The amount of barium carbonate added is 5g / L to 13g / L. If the amount of barium carbonate added is too small, the desired black Cr plating layer cannot be formed due to the remaining sulfate radicals, and conversely, if the amount is too large, the stability of the black Cr plating layer decreases, so the amount is more preferably 8g / L to 10g / L.
[0033] The amount of magnesium fluorosilicate added is specified to be in the range of 0.05 g / L to 0.3 g / L, preferably 0.1 g / L to 0.2 g / L. The amount of magnesium fluorosilicate added affects the hue of the black Cr plating layer, so the amount is set to the above range to form the black Cr plating layer.
[0034] Phosphoric acid is added in an amount of 6 mL / L to 12 mL / L as an aqueous solution with a concentration of 85 wt %.
[0035] The plating bath contains magnesium silicofluoride, sodium nitrate and phosphoric acid in addition to chromium anhydride and barium carbonate to prevent the occurrence of fine cracks and produce a stable black Cr plating layer. The amount of sodium nitrate added to the plating bath is specified to be within a very limited range of 2g / L to 5g / L, preferably 3.5g / L to 4.0g / L.
[0036] Furthermore, by adding 10 g / L to 20 g / L of oxalic acid and 1 g / L to 5 g / L of trivalent chromium to the plating bath, a more stable Cr plating layer can be formed.
[0037] The current density is preferably 25 A / dm 2 or 35A / dm 2 If the current density is too low or high, it is difficult to electrodeposit a desirable black Cr plating layer. The current density is also adjusted to an optimum value within the above range to obtain a perfect black or bluish black color according to the shape and application of the base metal, but more preferably, it is adjusted to 28 A / dm 2 or 32A / dm 2If the base metal is not flat but curved with a recessed shape, the current density at the recessed part will decrease, so the current density is adjusted to optimize the film thickness of the black Cr plating layer, taking into account the shape of the base metal.
[0038] The temperature of the plating bath can be set to 15°C to 25°C, so that the running costs can be reduced by keeping the temperature at room temperature without heating or cooling. The plating time can be set to 5 to 20 minutes.
[0039] The thickness of the black Cr plating layer is set to an optimum thickness for the application, but is thinner than the thickness of the hard Cr plating layer, and is preferably 0.1 μm or more and less than 10 μm.
[0040] [Example 1] (Hard Cr plating process) A hard Cr plating layer with a thickness of approximately 10 μm is applied to the surface of the pretreated base metal, which is an iron plate. The plating bath contains 250 g / L of chromic anhydride and 2.5 g / L of sulfuric acid. The plating bath temperature is 25℃, and the current is 30A / dm 2 for 30 minutes to deposit a hard Cr plating layer on the surface of the base metal.
[0041] (Black Cr plating process) A black Cr plating layer with a thickness of approximately 3 μm is applied to the surface of the hard Cr plating layer. The plating bath contains 400 g / L of chromic anhydride, 9 g / L of barium carbonate, 0.16 g / L of magnesium silicofluoride, 3.8 g / L of sodium nitrate, and 9 mL / L of an aqueous solution of phosphoric acid with a concentration of 85 wt%. The plating bath temperature was 20°C and the current density was 30A / dm 2 Then, using a graphite electrode as the anode, plating is performed for 10 minutes to form a black Cr plating layer on the surface of the hard Cr plating layer.
[0042] The metal plate prototyped using the above plating method, with an iron base metal, achieved excellent corrosion resistance with absolutely no rusting observed in a corrosion resistance test lasting approximately 700 hours, and also achieved heat resistance that did not discolor when heated to high temperatures of over 400°C. [Industrial Applicability]
[0043] The present invention provides a beautiful black Cr plating layer on the surface of a base metal, and can be effectively used in applications where high surface hardness and corrosion resistance are required. [Explanation of symbols]
[0044] 1…Base metal 2...Hard Cr plating layer 3...Black Cr plating layer 4. Crack
Claims
1. a hard Cr plating process for providing a hard Cr plating layer on the surface of the base metal; The hard Cr plating layer is used as a base plating layer, a black Cr plating step of laminating a black Cr plating layer on the hard Cr plating layer; In the black Cr plating process, 350 g / L to 450 g / L of chromic anhydride; In addition to 5 g / L to 13 g / L of barium carbonate, 0.1 g / L to 0.2 g / L of magnesium silicofluoride; 2 g / L to 5 g / L of sodium nitrate; A plating bath containing an aqueous solution of phosphoric acid at a concentration of 6 mL / L to 12 mL / L with a concentration of 85 wt % was used. Current density is 25 A / dm 2 to 35 A / dm 2 , The solution temperature is 15° C. to 25° C. The plating method is characterized in that the black Cr plating layer is formed by plating for 5 to 20 minutes.
2. 2. The plating method according to claim 1, The black Cr plating layer is It is thinner than the hard Cr plating layer, A plating method, characterized in that the thickness is 0.1 μm or more and less than 10 μm.
3. 3. The plating method according to claim 1 or 2, The thickness of the hard Cr plating layer is A plating method, characterized in that the thickness is 1 μm or more and 50 μm or less.
4. 2. The plating method according to claim 1, In the black Cr plating process, The plating bath is 10 g / L to 20 g / L of oxalic acid; A plating method comprising adding 1 g / L to 5 g / L of trivalent chromium.
5. 2. The plating method according to claim 1, In the black Cr plating process, The plating method according to the present invention is characterized in that the amount of chromic anhydride added is 360 g / L to 420 g / L.
6. 2. The plating method according to claim 1, In the black Cr plating process, The plating method is characterized in that the amount of barium carbonate added is 8 g / L to 10 g / L.
7. 2. The plating method according to claim 1, In the black Cr plating process, The plating method according to the present invention, wherein the amount of magnesium silicofluoride added is 0.15 g / L to 0.17 g / L.
8. 8. The plating method according to claim 1, further comprising the steps of: The black Cr plating process is The plating method is characterized in that the plating time is 8 to 15 minutes.
Citation Information
Patent Citations
Black color chrome plating solution
JP1980041942A
Plating method for black chromium
JP1981009391A
Two-tone plating film
JP1984197588A
Manufacture of sheathing parts for timepiece
JP1986000594A
Metallic ornament and production of metallic ornament
JP1996283962A
